Pengaruh Pengembangan Karier dan Lingkungan Kerja Terhadap Kepuasan Kerja dan Dampaknya Terhadap Produktivitas Karyawan PT Prima Sejahtera Indonesia - Mohammad Jon Tasrif (Jurnal Manajemen FE-UB, 2021)
This study aims to examine and analyze the influence of factors related to employeeproductivity. These factors include Career Development and Work Environment, which later inthis study functioned as independent variables affecting Employee Productivity which functionedas the dependent variable, while Job Satisfaction is a variable that functions as an intermediaryvariable (intervening).The research method used in this research is path analysis. The results showed that therewas a direct effect of Career Development, Work Environment, Job Satisfaction on EmployeeProductivity.Career Development and Work Environment have a direct effect on Job Satisfaction. JobSatisfaction as an intervening variable is able to mediate the indirect effect of CareerDevelopment and Work Environment on Employee Productivity, with the results of the sobel test.Keywords: Career Development, Work Environment, Job Satisfaction, Employee Productivity